PERENCANAAN FASILITAS PENDIDIKAN KAWASAN PERKOTAAN - Wahyu Gia Uliantoro (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
East Bandung is an area with high population growth. As a consequence, this area needs additional social infrastructure, including education facilities. So far, there have been many parents who send their children to school out of this area. Thisraises queries about the quantity and quality of existing education infrastructure. The approach to investigate and evaluate the existing education facilities is by using the standards through Ministry of Education decree No. 24/2007. The result ofstatistic calculation shows the area needs additional elementary school plants in several 'kelurahans' (urban villages), and several junior and senior high school plants. In terms of distance, there are several schools which are quite distant based on the standard. In addition, there are only few schools meeting the minimum standard of plant width, building size, and school facilities. Meanwhile, there is no school fulfilling the minimum width for each school facility.